STRATEGI EFEKTIF INTERNALISASI NILAI KRISTEN DALAM PEMBENTUKAN KARAKTER DAN SPIRITUALITAS REMAJA KRISTEN - Ardianto Lahagu; Fransiskus Irwan Widjaja (Sekolah Tinggi Teologi Arastamar Bengkulu, 2024)
This study aims to identify effective strategies for internalizing Christian values in shaping the character and spirituality of Christian youth. This research explores theological literature relevant to Christian spiritual formation strategies using a descriptive qualitative approach and literature analysis. The findings reveal that using Bible stories, reflective discussions, social service, and the active involvement of pastors, families, and church communities are vital components in the internalization process of Christian values. A holistic approach integrating Biblical teaching with practical experience is highly effective in cultivating Christian youth character deeply rooted in solid spirituality. The originality of this research lies in the synergy between spiritual formation and the role of church communities in shaping youth spirituality, a topic that has rarely been explored in depth in contemporary theological literature.